Painful finger, diagnosis and surgical management: Clinical puzzle - Verma, Mukta; Singh, Manish (Indian Journal of Case Reports, 2018)
It is really very difficult to live with a painful finger. Here, we are discussing a case who presented with a complaint of severe lancinating pain in her left index finger for about 7 years. This pain was so distressing to her that she was requesting for the amputation of her finger. Being a reconstructive surgeon, it was really very difficult to fulfill her wish. In the past 7 years, she consulted to several practitioners but did not get relief of her pain. Clinical suspicion of Glomus tumor was made and magnetic resonance imaging was done to confirm the diagnosis. Surgical excision of the swelling was done, and the patient was completely relieved of her pain.